Hariri & Hariri Architecture. (Images Pub, 2017)
Regarded by critics to be one of the most progressive American firms to be seen in the last 30 years, Hariri & Hariri Architecture was established in 1986 by Iranian-born Cornell-educated sisters, Gisue Hariri and Mojgan Hariri. Their work imbues their own unique brand of modernism across conceptual, residential, commercial and institutional works. The practice has a voice that is distinctly its own. The firm's work has often been described in the language of poetry or art. What differentiates its work is the firm's insistence that it approaches all projects, small or large, in a 'holistic' manner. While this approach integrates multiples dimensions and considerations, there are two overriding imperatives that transcend others to define its design narrative: 'nature and identity.' These key principles are celebrated in this visually stunning book. 0A significant addition to IMAGES' growing list of titles in it's global-reaching Leading Architects series, this beautifully photographed book showcases an enormous body of work by a firm led by two multi-disciplinary practitioners.
Includes bibliographical references (pages 246-249).
Keywords: Hariri & Hariri (Firm); Architects -- United States; Architectural firms -- New York (State) -- New York; Architecture -- United States -- Pictorial works; Architecture, Modern -- Pictorial works